1977
DOI: 10.1111/j.1365-2672.1977.tb00753.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yeast Extract Concentration on Viability and Cell Distortion in Rhizobium spp.

Abstract: A low concentration of yeast extract (0·1%) in liquid media favoured rapid growth and high percentage of viable cells in cultures of Rhizobium japonicum (CB 1809), R. lupini (WU 425), R. meliloti (SU 47), R. trifolii (TA1) and a cowpea strain (CB 756). Concentrations of yeast extract > 0·35% depressed viability and produced distorted cells in all strains except SU 47: TA1 was especially sensitive. When used at 0·5–1% (w/v), each yeast extract (Difco, Oxoid, Vegemite) or casein hydrolysate produced greatly enla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Glycine toxicity in bacteria is a well-documented phenomenon and has been linked to a 20 to 40% decrease in the extent of cross-linking of the peptidoglycan and significant changes in cell morphology, including elongation, spheroplast formation, and rounding of rod-shaped cells (26). Yeast extract or glycine induces significant changes in cell morphology in some strains of Rhizobium spp., resulting in alteration of the typical rodshaped cells into enlarged, distorted, pleomorphic shapes and spheroplasts that sometimes resemble bacteroid cells (46,47). The RL3499-RL3502 mutants had similarly altered cell shape in the presence of glycine, providing further evidence for cell wall alterations in these mutants.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Glycine toxicity in bacteria is a well-documented phenomenon and has been linked to a 20 to 40% decrease in the extent of cross-linking of the peptidoglycan and significant changes in cell morphology, including elongation, spheroplast formation, and rounding of rod-shaped cells (26). Yeast extract or glycine induces significant changes in cell morphology in some strains of Rhizobium spp., resulting in alteration of the typical rodshaped cells into enlarged, distorted, pleomorphic shapes and spheroplasts that sometimes resemble bacteroid cells (46,47). The RL3499-RL3502 mutants had similarly altered cell shape in the presence of glycine, providing further evidence for cell wall alterations in these mutants.…”
Section: Discussionmentioning
confidence: 72%
“…Earlier research studying rhizobial growth has documented sensitivity to yeast extract and peptide sources such as hydrolyzed casein (46,47). In some reports this sensitivity was attributed to the presence of the amino acid glycine (46).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methyl blue reduction was observed by adding 1 drop of 1% methyl blue to a test tube of inoculated milk after 7 days of incubation at 28°C and then incubating the preparation at 37°C for 1 h; disappearance of the blue color was regarded as a positive reaction. Nile blue reduction was detected by using the method of Skinner et al (16). Urease was detected by the methods of Smibert and Krieg (17), whereas the catalase, phenyalaninase, oxidase, peroxidase, and cytochrome oxidase tests were those described by Skerman (15).…”
Section: Methodsmentioning
confidence: 99%
“…*Present address: P. G. Department of Botany, 'Utkal University (Vani Vihar), Orissa, India. 84 A. Misra et al Starch was identified by iodine staining, the presence of polyphosphate and glycogen was assumed on the basis of tests on similar materials (Dart & Chandler 1972;Skinner et al 1977); the presence of leghaemoglobin by pink coloration of the nodules. …”
mentioning
confidence: 99%